Reflections on JBCR Growth and Development - Charles R. Baxter (Journal of Burn Care & Rehabilitation, 1983)
Burn injuries among incarcerated individuals represent an underexplored intersection of medical ethics, correctional policy, and health equity. Although scholarship increasingly examines vulnerable groups such as refugees and undocumented patients, incarcerated burn patients remain largely absent. Dual loyalty-balancing duty to the patient with obligations to the institution or state-creates distinctive challenges that are intensified in burn care, where timely intervention, pain control, rehabilitation, and psychosocial support are critical but often constrained by security protocols and systemic neglect. We conducted a narrative review of PubMed, Embase, and Scopus to identify peer-reviewed articles, position statements, and ethical analyses addressing incarcerated healthcare, dual loyalty, and burn treatment (English-language, 2000-2025). A thematic synthesis identified recurring ethical tensions, clinical barriers, and potential frameworks for resolution. Findings highlight a major gap in both literature and professional discourse. Recurrent themes included restricted access to specialized burn centers, compromised informed consent under custodial oversight, inadequate rehabilitative services, and disproportionate suffering linked to institutional neglect. Dual loyalty emerged as a central driver of ethical conflict, often pitting patient dignity against correctional authority. Elevating incarcerated burn care within burn scholarship and advocacy is necessary to uphold standards of care. Explicit attention to dual loyalty can support reforms that preserve patient dignity while maintaining institutional safety, improve outcomes, and reaffirm professional ethical commitments.